2022
DOI: 10.1007/s10618-022-00847-y
|View full text |Cite
|
Sign up to set email alerts
|

TCMI: a non-parametric mutual-dependence estimator for multivariate continuous distributions

Abstract: The identification of relevant features, i.e., the driving variables that determine a process or the properties of a system, is an essential part of the analysis of data sets with a large number of variables. A mathematical rigorous approach to quantifying the relevance of these features is mutual information. Mutual information determines the relevance of features in terms of their joint mutual dependence to the property of interest. However, mutual information requires as input probability distributions, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 93 publications
(156 reference statements)
0
0
0
Order By: Relevance
“…The lack of this property may seriously mislead correlation measurement in practice. Pertinent studies have demonstrated that reliable estimates can be achieved by subtracting the expected value under the hypothesis of independence [25,26]. Inspired by this, we modify the estimator ĝ(C, v i ) by subtracting the bias under independent case, as delineated below.…”
Section: Network Structure Reconstructionmentioning
confidence: 99%
“…The lack of this property may seriously mislead correlation measurement in practice. Pertinent studies have demonstrated that reliable estimates can be achieved by subtracting the expected value under the hypothesis of independence [25,26]. Inspired by this, we modify the estimator ĝ(C, v i ) by subtracting the bias under independent case, as delineated below.…”
Section: Network Structure Reconstructionmentioning
confidence: 99%